HVDC and FACTS Controllers Applications of Static Converters in Power Systems - Sood, Vijay K. (Power Electronics and Power Systems, 2004)
HVDC and FACTS Controllers: Applications of Static Converters in Power Systems focuses on the technical advances and developments that have taken place in the past ten years or so in the fields of High Voltage DC transmission and Flexible AC transmission systems. These advances (in HVDC transmission and FACTS) have added a new dimension to power transmission capabilities. The book covers a wide variety of topics, some of which are listed below: -Current Source and Voltage Source Converters, -Synchronization Techniques for Power Converters, -Capacitor Commutated Converters, -Active Filters, -Typical Disturbances on HVDC Systems, -Simulation Techniques, -Static Var Compensators based on Chain Link Converters, -Advanced Controllers, -Trends in Modern HVDC. In addition to EHV transmission, HVDC technology has impacted on a number of other areas as well. As an example, a chapter dealing with HVDC Light applications is included providing recent information on both on-shore and off-shore applications of wind farms.